From Paper to Platform: Navigating the Digital Transformation and Integration Challenges of Health Information Systems - Mokke, Desya Dillachsyadina; Syamsinar, Sitti; Husdiningsih, Ferra; Radiastu, I Wayan Angga; Tombora, Djasrin H; Hernawati; Risky, Sartini (Green Publisher, 2026)
The digital transformation of health information systems (HIS) is a critical yet persistently challenging endeavor, often failing to deliver promised value due to a narrow, techno-centric focus. This study argues that successful transformation is fundamentally a socio-technical co-optimization problem, requiring simultaneous attention to interdependent technical, organizational, and human dimensions. Through an integrative literature review and conceptual framework analysis, we identify and categorize a multidimensional landscape of barriers, including legacy system inertia, interoperability gaps, fragmented governance, workflow misalignment, clinician resistance, and cultural friction. These challenges are not isolated but are dynamically interconnected, as visualized in a network dependency model, where a flaw in one dimension exacerbates problems in another, creating cycles of failure. To navigate this complexity, we propose a actionable socio-technical framework that translates theory into practice. The framework prescribes integrated strategic enablers: leadership must champion iterative, user-centered design and inclusive governance; technical strategy must adopt open standards and modular architecture; and a foundational culture of psychological safety and continuous learning must be fostered. The findings underscore that sustainable transformation is not a technology installation project but a long-term organizational evolution, demanding a balanced portfolio of initiatives to cultivate an adaptive learning healthcare ecosystem.